2005
DOI: 10.1111/j.1365-2958.2005.04484.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping binding residues in the Plasmodium vivax domain that binds Duffy antigen during red cell invasion

Abstract: Summary Plasmodium vivax depends on interaction with the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
102
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 40 publications
8
102
0
1
Order By: Relevance
“…Although polymorphic residues were widely distributed throughout the PvDBPII sequence, polymorphisms at residues 417, 437, and 503, either in single or in combination, can affect the efficacy of inhibitory antibodies against erythrocyte binding [23,35]. As these residues compose an important discontinuous epitope in PvDBP, which might be the main target for inhibitory antibodies, these polymorphisms could be subject to immune pressure responsible for parasite escape from the host immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although polymorphic residues were widely distributed throughout the PvDBPII sequence, polymorphisms at residues 417, 437, and 503, either in single or in combination, can affect the efficacy of inhibitory antibodies against erythrocyte binding [23,35]. As these residues compose an important discontinuous epitope in PvDBP, which might be the main target for inhibitory antibodies, these polymorphisms could be subject to immune pressure responsible for parasite escape from the host immune system.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that this strong positive selection pressure in PvDBPII promotes greater diversity [14,30]. The immune pressure drives the generation of new PvDBP variants that are still able to bind erythrocytes but become resistant to inhibitory antibodies, suggesting that this DBP region is under positive pressure at critical residues and under negative pressure at the residues involved in receptor recognition [22,23,35]. A low prevalence of variant N417K (38.9%) was observed among Myanmar isolates, but more than 50% of W437R (61.1%) and I503K (77.8%) were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of site-directed mutagenesis data suggests that additional residues, other than those identified above, are involved in the DARC binding site or have a role in receptor recognition [11,12]. Mutations that completely abrogated P. vivax DBP binding to the DARC receptor map to multiple locations on the DBL structure outside of the proposed binding groove and a number of those residues cluster together on the outer surface of the DBL structure, including residues in unstructured exposed regions (e.g., PkDBPα DBL H59, S60).…”
Section: Proposed Darc Recognition Sitementioning
confidence: 98%
“…Based on previous mutational analysis [10][11][12], key residues for DARC recognition were identified as a cluster of nonpolar residues (Y94, L168, I175) grouped adjacent to basic residues (K96, K100, R103, K177) on the subdomain 2 surface to promote interaction with the sulfated Y41 of DARC, a critical element for receptor recognition identified in in vitro assays [13]. Major conformational changes to the P. knowlesi DBPα DBL structure are not predicted for DBL-DARC interaction, although this interaction is thought to bring the subdomain 3 loop into close contact with the host cell surface possibly to stabilize the ligand-receptor interaction or lead to a subsequent event in invasion.…”
Section: Proposed Darc Recognition Sitementioning
confidence: 99%
See 1 more Smart Citation